2020
DOI: 10.15252/embj.2019103315
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy mediates temporary reprogramming and dedifferentiation in plant somatic cells

Abstract: Somatic cells acclimate to changes in the environment by temporary reprogramming. Much has been learned about transcription factors that induce these cell‐state switches in both plants and animals, but how cells rapidly modulate their proteome remains elusive. Here, we show rapid induction of autophagy during temporary reprogramming in plants triggered by phytohormones, immune, and danger signals. Quantitative proteomics following sequential reprogramming revealed that autophagy is required for timely decay of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 75 publications
(92 reference statements)
8
62
0
Order By: Relevance
“…An unexpected finding in the present study is that a second phase of autophagy is induced upon reoxygenation, with autophagosomes appearing and peaking within minutes of the return of molecular oxygen followed by gradual disappearance as recovery proceeds. Recent work suggests that similar rapid and transient autophagic bursts may be a common reprogramming response to several hormonal and environmental signals that helps facilitate the rapid removal of unnecessary cellular components, and is necessary for the establishment of new programs (Rodriguez et al, 2020). In this regard, it important to consider that the post-hypoxia reoxygenation triggers a complex metabolic reprograming response as well as generating its own set of stresses.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected finding in the present study is that a second phase of autophagy is induced upon reoxygenation, with autophagosomes appearing and peaking within minutes of the return of molecular oxygen followed by gradual disappearance as recovery proceeds. Recent work suggests that similar rapid and transient autophagic bursts may be a common reprogramming response to several hormonal and environmental signals that helps facilitate the rapid removal of unnecessary cellular components, and is necessary for the establishment of new programs (Rodriguez et al, 2020). In this regard, it important to consider that the post-hypoxia reoxygenation triggers a complex metabolic reprograming response as well as generating its own set of stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Primary root tips were excised and collected into liquid nitrogen. Tissue lysis, sample preparation, protein labeling, Tandem-Mass-Tag (TMT) spectrometry, MS/MS data analysis, and TMT-quantifications were performed as recently described (Rodriguez et al, 2020; Stephani et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Autophagic puncta accumulate in these reprogramming cells, and autophagy inhibition blocks transdifferentiation initiation, whereas autophagy stimulation (by blocking mTORC1) increases its efficiency and efficacy. The requirement of autophagy for plasticity may be universal as even plant cells use autophagy for climatic adaptation (Rodriguez et al, 2020). Accordingly, Dr Mishra showed that autophagy is also required for transdifferentiation of pancreatic duct cells into endocrine cells.…”
Section: Towards a Common Program Governing Cellular Plasticitymentioning
confidence: 99%